2009
DOI: 10.1158/1535-7163.mct-09-0459
|View full text |Cite
|
Sign up to set email alerts
|

Activity of dasatinib againstL576P KITmutant melanoma: Molecular, cellular, and clinical correlates

Abstract: Point mutations in the KIT receptor tyrosine kinase gene have recently been identified in mucosal, acral lentiginous, and chronically sun-damaged melanomas. We have identified the first human melanoma cell line with an endogenous L576P mutation, the most common KIT mutation in melanoma ( 30-40%). In vitro testing showed that the cell viability of the L576P mutant cell line was not reduced by imatinib, nilotinib, or sorafenib small molecule KIT inhibitors effective in nonmelanoma cells with other KIT mutations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(120 citation statements)
references
References 29 publications
5
113
1
1
Order By: Relevance
“…Plates were incubated at 37 o C in a humidified atmosphere of 5% CO 2 and air mutation, marked regression of disease was observed following dasatinib treatment. 24 As demonstrated here, the B16-OVA melanoma cell line does not carry the L576P Kit mutation which is consistent with the resistance demonstrated here of this cell line to dasatinib treatment. Collectively, these findings suggest that dasatinib should be targeted to specific activating mutations where the best therapeutic results can be achieved.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Plates were incubated at 37 o C in a humidified atmosphere of 5% CO 2 and air mutation, marked regression of disease was observed following dasatinib treatment. 24 As demonstrated here, the B16-OVA melanoma cell line does not carry the L576P Kit mutation which is consistent with the resistance demonstrated here of this cell line to dasatinib treatment. Collectively, these findings suggest that dasatinib should be targeted to specific activating mutations where the best therapeutic results can be achieved.…”
Section: Discussionsupporting
confidence: 90%
“…21 Dasatinib blocks the activity of other SFKs (Lyn, Fgr, Blk, Hck, Fyn, Yes and Lck) at nanomolar concentrations, 22 and it also blocks the activity of the Kit receptor tyrosine kinase bearing activating mutations such as L576P. 23,24 Dasatinib impairs the migration and invasion of different human melanoma cell lines 25,26 including a cell line that expresses L576P mutant Kit where dasatinib treatment induces apoptosis and slows growth. 26,23 Notably, clinical activity of dasatinib is evident in the marked tumor regressions observed in dasatinib-treated patients whose melanomas harbor the L576P Kit mutation.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that in these less-sensitive mutations, increased levels of imatinib or an alternative kinase inhibitor is required. Dasatinib has since been shown to have a selective inhibitory effect in this KIT mutation both in vitro and in the clinic in the setting of previous imatinib therapy (Woodman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has also been reported that the melanoma patients harboring the activating mutations in the KIT receptor exhibited a partial or complete response to imatinib mesylate [33] . It has however been noted that dasatinib was more effective than imatinib at reducing the viability of melanoma cells in two melanoma patients harboring the KIT L576P mutation which is the most frequent KIT mutation occurring in approximately 30%-40% cases of melanoma [44] . Furthermore, the data from a multi-institutional phase II trial with an oral multikinase inhibitor termed sorafenib, which targets different tyrosine protein kinases, including wild-type and mutant B-Raf and C-Raf kinases, PDGFRs, KIT, VEGFR2 and VEGFR3, performed with 36 patients with advanced melanomas have indicated that 1 patient showed a partial response for 175 d and 3 patients had stable disease with a mean duration of 37 wk [125] .…”
Section: Molecular Targeting Strategiesmentioning
confidence: 99%